The anti-apoptotic Coxiella burnetii effector protein AnkG is a strain specific virulence factor - Schäfer, Walter; Schmidt, Tamara; Cordsmeier, Arne; Borges, Vítor; Beare, Paul A.; Pechstein, Julian; Schulze-Luehrmann, Jan; Holzinger, Jonas; Wagner, Nicole; Berens, Christian; Heydel, Carsten; Gomes, João Paulo; et al. (Scientific Reports, 2020)
The ability to inhibit host cell apoptosis is important for the intracellular replication of the obligate intracellular pathogen Coxiella burnetii, as it allows the completion of the lengthy bacterial replication cycle. Effector proteins injected into the host cell by the C. burnetii type IVB secretion system (T4BSS) are required for the inhibition of host cell apoptosis. AnkG is one of these anti-apoptotic effector proteins. The inhibitory effect of AnkG requires its nuclear localization, which depends on p32-dependent intracellular trafficking and importin-α1-mediated nuclear entry of AnkG. Here, we compared the sequences of ankG from 37 C. burnetii isolates and classified them in three groups based on the predicted protein size. The comparison of the three different groups allowed us to identify the first 28 amino acids as essential and sufficient for the anti-apoptotic activity of AnkG. Importantly, only the full-length protein from the first group is a bona fide effector protein injected into host cells during infection and has anti-apoptotic activity. Finally, using the Galleria mellonella infection model, we observed that AnkG from the first group has the ability to attenuate pathology during in vivo infection, as it allows survival of the larvae despite bacterial replication.
CRIS-Team Scopus Importer:2020-10-02